MANAGEMENT OF PSYCHOSOCIAL RISKS IN THE EDUCATIONAL SECTOR OF LATVIA - Jemeljanenko, Antonina; Geske, Andrejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Risk management is gaining acknowledgement in organisational management due to the benefits it brings with it, such as ability of managers to forecast possible threats and plan the most appropriate prevention measures. Psychosocial risk group is one of the largest risk group types and is related to the aspects of staff overburning, lack of employee motivation, health problems due to stress, etc. Study carried in Latvia about risk management showed that psychosocial risks are significant for educational institutions. Empirical research carried out in Latvia has shown that the top risks perceived by the education sector professionals in Latvia are overloading of employees and lack of employee motivation. Hypothesis of this study is that psychosocial risks, such as overloading and lack of motivation, are not dealt well with due to low awareness of effective psychosocial risk management techniques. There was no profound research performed on this topic in Latvia in the last ten years. The aim of this study is to explore different methods researched by other authors how the risk can be managed, analyse causes of these risks and provide the recommendation on how to deal with the psychosocial risks in the educational sector.